Prize essay on the jurisdiction of the local courts in Ireland, Scotland, and England compared - Dodd, William H. (Statistical and Social Inquiry Society of Ireland, 1877)
The Council of this Society have done me the honour of selecting me as essayist ?On the difference of division of jurisdiction between Local and Central Courts in Ireland, Scotland, and England?. I have inquired into the matters on which the Council have desired me to write, and I respectfully submit to the Society the result of my inquiry.
Read before the Society, 23 January 1877
Keywords: Local court jurisdiction; Irish legal system; Civil Bill Courts; Sheriffs' Courts; County Courts; 314.15